Perbandingan Media Alternatif Kacang Kedelai dan Media Nutrient Agar Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Nurhidayanti Nurhidayanti (Indobiosains, 2022)
Nutrient Agar media is a medium with a yellowish white powder and after use it will be solid because it contains agar. The most important content contained in this medium is carbohydrates as well as protein contained in meat extract and peptone according to the needs of most bacteria. (Rossita, 2015). Soybeans are one of the natural ingredients that contain high enough protein. The purpose of the study was to compare the number of Staphylococcus aureus bacteria colonies on nutrient agar media and soybean media. The type of research used is experimental. This research was conducted on 21-25 June 2021 at the Palembang Health Laboratory Center with a total of 32 samples. Data were analyzed using Mann Whitney Test. The results showed that the average number of colonies on soybean media had an average of 3.3 colonies, while colonies on nutrient agar media had an average of 50.4 colonies. Statistical test results obtained p = 0.000 means that there is a comparison of the number of colonies of Staphylococcus aureus bacteria on nutrient agar media and soybean media. The conclusion of this study is that soybean media cannot be used as an alternative medium for the growth of Staphylococcus aureus bacteria. Keywords: Nutrient Agar, Soybeans, Staphylococcus aureus